A New Trend in Media and Library Collaboration within Citizen Science? The Case of ‘A Healthier Funen’ - Kaarsted, Thomas; Overgaard, Anne Kathrine (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
Beginning in 2017 three major institutions on the island of Funen, Denmark, collaborated on a Citizen Science project: “A Healthier Funen” (AHF). The partners were a university, a university hospital and a regional broadcaster. The project invokes citizens to vote for the allocation of research funding.In the case study presented here, we analyze the Citizen Science aspects of AHF and the roles of libraries as collaborators, we examine the results and the reach of the project, and we argue that this strand of Citizen Science could be a possible new trend for Library, Faculty and media collaboration.Seen against the background of the scope and definitions of Open Science and LIBER’s Open Science Roadmap, the case of AHF suggests that the field of Citizen Science bears great potential in regard of providing a new level of innovation for Libraries: through a collaborative professional approach to science communication, libraries can assume a strategic role together with the Faculty staff.In the context of reciprocality within Citizen Science, the Library can build skills for engaging in projects, adopt toolkits or models, as well as participate in the recruitment and retention processes for staff/volunteers, participate in marketing activities and promote a positive attitude towards Citizen Science, thus creating an increased Public Understanding of Science, as the underlying public service criteria are seen in at least 31 countries.